Prophylaxis use of clotting factor replacement products in people with non‐severe haemophilia: A review of the literature. Issue 1 (12th October 2022) - Iorio, Alfonso; Königs, Christoph; Reding, Mark T.; Rotellini, Dawn; Skinner, Mark W; Mancuso, Maria Elisa; Berntorp, Erik
Abstract: Introduction: People with non‐severe haemophilia appear to be under‐treated in many countries, and this may lead to joint damage and worsen quality of life. Aim: To review literature for clotting factor replacement prophylaxis in people with non‐severe haemophilia A and B (HA/HB) in relation to long‐term outcomes to support clinical decision‐making. Methods: A targeted literature search was performed to identify studies published between 2000 and 2021 that included prophylaxis in people with non‐severe HA/HB and long‐term outcomes, including annualized bleeding rates, joint health and quality of life. Results: Although eligible articles included 2737 and 2272 people with mild or moderate HA, respectively, only 22% ( n = 609) and 29% ( n = 668) reported treatment regimens. A total of 549 people with moderate HA were treated with factor replacement prophylaxis and were from high‐income countries. On the contrary, nearly all people with mild HA received desmopressin ( n = 599). Details of treatment regimens for women with haemophilia and people with HB were sparse. Three studies provided long‐term outcomes for people with moderate haemophilia who received prophylaxis with factor concentrate, supporting early prophylaxis in people with a frequent bleeding phenotype regardless of their endogenous clotting factor level to preserve joint health. Conclusion: There remain large knowledge gaps when considering how to provide optimal treatment for people with non‐severe haemophilia. Nonetheless, there is a strong rationale that prophylaxis should be considered early in life according to similar strategies as for severe haemophilia for those with a frequent severe bleeding phenotype.